'God has breathed into us the breath of life' – Jewish and Christian approaches to breathing meditation in an Australian context. Issue 3 (27th May 2019) - Mudge, Peter
ABSTRACT: Breathing meditation (BM) in both Jewish and Christian contexts focuses on the breath as the vivifying Spirit, Holy Spirit or life force. A flourishing theology of the body must of necessity be an 'embodied spirituality', and ought to encompass a biblical and spiritual theology of the whole person. This article demonstrates the practicality of this BM technique by outlining possible approaches during a typical week within an Australian context. The article explores a shorter series of 'dawn to morning meditations' through the lens of Judaism, and another complementary, longer suite for the 'afternoon to night' period based on the Christian tradition, including one meditation based on Australian Aboriginal spirituality. Each meditation exercise could be adapted for either adults, senior students or primary students. All exercises, apart from the Dadirri and name of G-d examples, are original compositions trialled by the author.